Examining the Relationship Between Race and Juvenile Court Decision-Making: A Counterfactual Approach - Gann, Shaun M. (Youth violence and juvenile justice, 2019)
Prior research has found that disproportionate minority contact (DMC) is a problem at various decision-making points in the juvenile justice system. This study addresses two limitations often found in prior DMC research: (1) a focus on a single court and/or a single stage of the juvenile court process and (2) methodological problems in comparing youth of different races who are otherwise similarly situated. Nearest neighbor matching is used to examine the relationship between race and five juvenile court outcomes—pre-adjudication detention, case dismissal, adjudication, secure confinement, and waiver to criminal court—in a sample of over 50,000 youth referred to seven juvenile courts. After matching youth on multiple legal and extralegal variables, results indicate that non-White youth were significantly more likely than White youth to be detained prior to adjudication, placed in a secure confinement facility postadjudication, and waived to criminal court.